Effect of Plant spacing of Paspalum atratum that was Fertilized with Mikoriza arbuskula on Productivity - Poetri, Eko (FAPETKAN UNTAD, 2019)
This experiment was aimed to examine the best plant spacing of Paspalum sp productivity that was fertilized with Arbuscular mycorrhizal in different plant spacing. The research was conducted in deer captivity area of Darmaga Research Forest, Forest Research and Development Center of The Ministry of Forestry. Model used was a randomized block design with 5 replications. The treatments were plant spacing, i.e. 30 x 30 cm, 40 x 40 cm, dan 50 x 50 cm. The results showed that Paspalum atratum grass fertilized by arbuscular mycorrhizal as 30 spore/5 kg soil by 40 cm Ã— 40 cm plant spacing had the best production potential and nutritive value with the highest number of tillers( 30.80 at 30 DAP), shoot DM (88.76 g at 30 DAP), fresh weight (1021 g/mÂ² at 30 DAP), DM content (11.10%), DM digestibility (57.88%), OM digestibility (53.74%), digested DM production (66.07 g), digested OM production (55.07 g), DM production (112.94 g), OM (101.19 g), and CP (12.26 g).Keyword: Plant spacing, Nutritive value, Arbuscular mycorrhizal, Paspalum atratum.